How open hardware drives digital fabrication tools such as the 3D printer - Johan Söderberg (Internet Policy Review, 2013)
A case study of hobbyists developing a desktop 3D printer, indicative of a broader movement around open hardware development, is used to advance a theoretical apparatus drawing on social movement research. This is proposed as an alternative to how innovation by users is typically studied in innovation studies literature, namely, as discrete, isolated cases. Open hardware development projects make up a larger ecology, held together by common ideas, a shared communication infrastructure, conferences and licenses, among other things, and it therefore makes sense to look at them as part of a single movement.
Keywords: 300; Digital fabrication; 3D Printer; Innovation; Open hardware; Arduino; Ronja; Rep-rap; Hardware